Pengaruh Program Jalan Kaki 30 Menit Terhadap Tekanan Darah Pada Penderita Hipertensi Terkontrol Di Kota Padangsidimpuan - Harahap, Mei Adelina; Gintings, Akhyar Fauzi; Rangkuti, Nur Aliyah; Rangkuti, Juni Andriani (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Hypertension is a condition in which a person experiences an increase in blood pressure above normal. In general, blood pressure is high when the systolic blood pressure is more than 120 mmHg and the diastolic blood pressure is more than 80 mmHg. The purpose of this study was to determine the effect of a 30-minute walk program on reducing blood pressure in controlled hypertension patients. This research method is quantitative with the design used in time series research, the population in this study amounted to 9,448 respondents and a sample of 15 respondents, it can be seen that the comparison of blood pressure in respondents before and after a 30-minute walk program using the Wilcoxon test obtained the value P-value = 0.000 (<0.05), the results of the study showed that there was a significant effect of the 30-minute walk program on reducing controlled blood pressure in patients with hypertension. The conclusion of this study is that non- pharmacological therapy such as a 30-minute walk program is an alternative treatment for reducing blood pressure in controlled hypertension patients. Suggestions for people with controlled hypertension should walk for 30 minutes regularly so that blood pressure is stable and avoid complications that will occur.